Dual-Resonant Implantable Circular Patch Antenna for Biotelemetry Communication - Rongqiang Li; Shaoqiu Xiao (International Journal of Antennas and Propagation)
A compact broadband implantable circular patch antenna is designed and experimentally demonstrated for Medical Implant Communications Service (MICS) band (402–405 MHz). Compared with other similar implantable antennas, the proposed antenna incorporates three advantages for biotelemetry communication. First, it can realize a broad impedance bandwidth by exhibiting dual resonances. Second, it can obtain a compact structure by introducing two arc-shaped slots, a rectangular slot and a circular slot on metal radiating patch. Finally, it can display a friendly shape by using a circular structure. The proposed antenna occupies a volume of about 431.5 mm3 (10.42 × 1.27π mm3), which is a compromise between miniaturization and bandwidth. The measured −10 dB impedance bandwidth is 55 MHz (385–440 MHz). Furthermore, the radiation performance and human body safety consideration of the antenna are examined and characterized.